Earthquake science in resilient societies. Issue 4 (20th April 2017) - Stahl, T.; Clark, M. K.; Zekkos, D.; Athanasopoulos‐Zekkos, A.; Willis, M.; Medwedeff, William; Knoper, Logan; Townsend, Kirk; Jin, Jonson
Abstract: Earthquake science is critical in reducing vulnerability to a broad range of seismic hazards. Evidence‐based studies drawing from several branches of the Earth sciences and engineering can effectively mitigate losses experienced in earthquakes. Societies that invest in this research have lower fatality rates in earthquakes and can recover more rapidly. This commentary explores the scientific pathways through which earthquake‐resilient societies are developed. We highlight recent case studies of evidence‐based decision making and how modern research is improving the way societies respond to earthquakes. Key Points: The level of seismic risk depends in part on societal investment in earthquake science Multidisciplinary investigations involving earthquake scientists and engineers greatly reduce casualties in earthquakes Recent examples highlight the utility of earthquake science in building resilient societies and the need for further research to reduce seismic risk